Mitigasi Pembiayaan Mudharabah Perbankan Syariah di Indonesia Melalui Pendayagunaan Cash Waqf Fund - Al Jawi, Amin; Siregar, Saparuddin; Sugianto, Sugianto (Universitas Islam Negeri Sunan Kudus, 2022)
This paper aims to uncover the main problem as well as to offer alternative solutions to the realization of mudharabah financing for Islamic banks in Indonesia, which is still 3% as of June 2021, through optimizing the role and authority of Islamic banks in the management of cash waqf. This study uses a descriptive method with a qualitative approach. The main problem of mudharabah financing is the high risk of loss of Islamic banks which have the potential to be unable to provide profit sharing to their depositors (negative profit sharing), therefore Islamic banks must look for alternative sources of deposits with a return rate of 0%, one of which is a source of cash waqf. By regulation, currently the authority of Islamic banks in the management of cash waqf is still limited to cashiers (traffic cash waqf funds) with their position as LKS-PWU. To increase mudharabah financing through cash waqf sources, Islamic banks must optimize their role as Nazhir through changes to Law Number 41 of 2004 and its derivation regulations, so that the money waqf funds that have been collected can be directly channeled to productive and prospective sectors for economic empowerment of the people through mudharabah financing. In addition, Islamic banks can reproduce the profits from the financing to the micro business sectors, the poor, and/or other sectors so that the profit-oriented and social-oriented missions of Islamic banks can run in a balanced way.